The suffering womanhood in Luke 13:10–17 in the context of the post-COVID-19 pandemic in Africa - Etukumana, Godwin A. (HTS teologiese studies, 2024)
The suffering of womanhood and maltreatment are apparent when reading ancient writings. In Luke 13:10–17, it is possible to see how a number of women who suffered illnesses were treated in the hands of religious elites of the ancient world. However, the woman in Luke’s encounter with the Lukan Jesus during her illness redefined how religious leaders should deal with the suffering of womanhood. The woman was healed and treated with dignity by the Lukan Jesus in the Gospel of Luke. Using socio-historical interpretation, the Lukan Jesus in the Gospel of Luke demonstrated that religion should be used to alleviate the suffering of women, not to exacerbate it. The lesson derived from the Lukan Jesus’ action and words on the suffering woman in Luke 13:12 is significant for the African religious setting in an endeavour to alleviate women’s suffering in Africa in the coronavirus disease 2019 (COVID-19) pandemic era.Contribution: This article adds to the ongoing discussion in biblical studies about gender equality, specifically in Africa where diseases such as COVID-19 have highlighted the need for change. It argues that African women should resist negative male dominance in society, similar to the woman in Luke, and work towards empowering women in Africa to achieve freedom and equality.